2021
DOI: 10.3889/oamjms.2021.6213
|View full text |Cite
|
Sign up to set email alerts
|

Association between Three Variants in the PRKAA2 gene, rs2796498, rs9803799, and rs2746342, with 10-year ASCVD Risk on Newly Diagnosed T2DM in Yogyakarta, Indonesia

Abstract: BACKGROUND: AMPK has pivotal roles in glucose and lipid metabolism, including  AMPKa2, which PRKAA2 encodes. Metformin as an anti-hyperglycemia agent acts through AMPK. Poor glycemia control among patients with type 2 diabetes mellitus (T2DM) could increase atherosclerosis cardiovascular disease (ASCVD) risk. Therefore, PRKAA2 genetic variation might contribute to 10-year ASCVD risk in patients with newly diagnosed T2DM receiving monotherapy metformin. AIM: The study aimed to detect an association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“… 27 , 28 Virginia et al in 2021 demonstrated that the PRKAA2 genetic variation (rs9803799) had a significant association to cardiovascular risk among patients with T2DM receiving monotherapy metformin. 29 …”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 Virginia et al in 2021 demonstrated that the PRKAA2 genetic variation (rs9803799) had a significant association to cardiovascular risk among patients with T2DM receiving monotherapy metformin. 29 …”
Section: Introductionmentioning
confidence: 99%